Peningkatan Kompetensi Profesional Guru dalam Menyusun RPP melalui Supervisi Kelompok di MIS AlMustajab Kec. Pulau Petak - Muslim (Jurnal Pendidikan Madrasah, 2022)
This research aims to describe the implementation of group supervision activities to improve the professionalism of teachers in compiling RPPs in MIS AlMustajab, Pulau Petak Subdistrict. This research uses action research methods consisting of 2 cycles including preparatory, planning, implementation, observation, and assessment activities. Data collection techniques use observations, Q&A and questionnaires. Data analysis methods use flow models, namely data reduction, data presentation, and conclusion draw. The results showed that group supervision activities can increase teacher professionalism in preparing RPP with the criteria for action success has passed in the 2nd cycle, which reaches a score of 90% (Excellent). The coaching model through a group supervision approach as one of the coaching models that can improve the professional competence of teachers can be utilized in teacher coaching by madrasah heads and supervisors.